Mechanoreceptor-inspired in-ear triboelectric sensor for unconstrained physiological monitoring and human–machine interaction - He, Qiang (2023)
Recently emerged wearable electronics intended for human–machine interfaces and on-body healthy monitoring present undesired constraints on the human body despite considerable efforts to be flexible and more skin-compliant. In addition, the bulky back-end signal processing circuits hinder the miniaturization integration and commercialization of these wearable devices. Here, we propose a mechanoreceptor-inspired ear-worn triboelectric sensor which realizes unconstrained facial expression monitoring, such as eye and mouth motion, as well as demonstrating a hands-free typing system based solely on eye movements. The integration of an organic electrochemical transistor with low power consumption and high output current can amplify the current signal of the triboelectric sensor by at least 3 orders, enabling accurate extraction of minute pressure changes stimulated by pulse wave in the ear canal. In addition, the signal retention capability endowed by the organic electrochemical transistor enables an expanded control mode, which is demonstrated in an eye-triggered music playback control system. Our work presents the immense potential of ear-worn triboelectric sensor for unencumbered health monitoring and seamless human–machine interaction.